CONDITIONS OF CAPTURE FISHERIES IN THE COASTAL AREA OF BATAM ISLAND KEPULAUAN RIAU PROVINCE - Hendrayana, Angga Sucitra; Sari, T. Ersti Yulika; Malau, Albert Gamot; Brown, Arthur; Panggabean, Donwill; Nazzla, Rauzatul (Jurnal Perikanan Unram, 2025)
The coastal area of Batam Island have a fairly high potential for capture fisheries and contribute to the community's economy, especially in coastal areas. Capture fisheries businesses must pay attention to economic and ecological sustainability. The purpose of this study is to analyze the sustainability of the capture fisheries business on Batam Island based on bio-economic aspects in order to provide an overview of fisheries business management. The analysis was carried out descriptively through the Gordon-Schaefer model approach with the Gordon logistics growth function. The analysis was carried out on three management conditions, namely Maximum Sustainable Yield (MSY), Maximum Economic Yield (MEY), and Open Access Equilibrium (OAE). The results of the study show that the optimal utilization of capture fisheries in the coastal area of Batam Island is around 7,823 units of fishing vessels every year. The production of catch in the Maximum Sustainable Yield condition is around 36,982 tons, in the the Maximum Economic Yield condition is around 36,977 tons, while in the Open Access Equilibrium condition is only around 1,646 tons.